1997
DOI: 10.1177/155335069700400107
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Antegrade Sphincterotomy

Abstract: The authors describe the technique and results of laparoscopic antegrade sphincterotomy. The procedure was performed in 42 selected cases of choledocholithiasis. The indications for attempting laparoscopic antegrade sphincterotomy included impacted stones in the papilla, multiple common bile duct stones, one or more common hepatic or intrahepatic stones, dilated common bile duct requiring a drainage procedure, suspicion of papillary stenosis, whenever numerous fragments are found after lithotripsy, and as an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…[53] who treated ten patients with transcystic saline flushing after dilation of the papilla. Results of unique techniques have been reported by other authors [61,62,63]. Ido et al [61] reported the results of laparoscopic transcystic cholangioscopy with lithotripsy.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…[53] who treated ten patients with transcystic saline flushing after dilation of the papilla. Results of unique techniques have been reported by other authors [61,62,63]. Ido et al [61] reported the results of laparoscopic transcystic cholangioscopy with lithotripsy.…”
Section: Resultsmentioning
confidence: 87%
“…In their experience, this approach was succesful in 78.5% of cases when used alone and in 92.9% of cases when other transcystic clearing methods were used. De Paula et al [62] and Curet et al [63] described the results of laparoscopic antegrade sphincterotomy. They reported no mortality, no major complications and no recurrence of papillary stenosis in a follow-up of 1-18 months [62] and 5 months [63]), respectively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In this article, we report our experience during the first 2 years of combining LC with IO-ERCP, using a modified version of the techniques previously described in the literature [7,10,14].…”
mentioning
confidence: 99%
“…The laparoscopist may then employ standard stone extraction techniques as well as flexible choledochoscopy and lithotripsy to clear the duct. Ampullary balloon dilation [71] and antegrade sphincterotomy under endoscopic observation [72] have both been performed with transcystic LCBDE to maximize duct clearance. A few surgeons have also successfully performed laparoscopic choledochotomy, a highly challenging procedure which enhances access to the proximal biliary tree and is usually followed by T-tube placement.…”
Section: Laparoscopic Common Bile Duct Explorationmentioning
confidence: 99%